The role of expenditure components in determinantion of import demand: Empirical evidence from Pakistan - Muhammad Irfan Chani; Amatul R. Chaudhary (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
This study is aimed at in-depth empirical analysis of impact of final expenditure components on import demand in Pakistan. ARDL bound testing approach to cointegration is used to analyze the long run relationship of import demand, relative prices of imports and components of final expenditure like household consumption, investment, exports and government consumption expenditures. Empirical results show that there exists a long run relationship between import demand and the macro components of final expenditure and relative prices. Long run coefficients indicate that elasticity of import demand with respect to different macro components of final expenditure is different. The impact of the all expenditure components on import demand is positive and significant. The relative prices have negative but insignificant relationship with import demand in Pakistan. For the analysis of Short Run dynamics, Vector Error Correction Model (VECM) has been used. The results show that all expenditure components have positive and significant impact on import demand in Pakistan while the effect of relative prices is also statistically insignificant in short run.
Keywords: 330; Import Demand; Expenditure Components; Relative Prices; Importnachfrage; Relativer Preis; Privater Konsum; Kointegration; Kointegration; Pakistan